From smart concept to challenging practice: How European regions deal with the Commission's request for novel innovation strategies - Henning Kroll; Emmanuel Muller; Esther Schnabl; Andrea Zenker (Fraunhofer Institute for Systems and Innovation Research ISI, 2014)
[Summary and Discussion] In summary, our findings suggest that the current efforts towards fulfilling the RIS3 ex-ante conditionalities are neither likely to trigger an immediate revolution in European regions' approaches towards innovation policy nor will they put an immediate or even rapid end to all the inherent challenges and contradictions of structural funding that have emerged and evolved across decades of past support periods. [...]
urn:nbn:de:0011-n-2892733
Keywords: 330